THE TANGIBLE USER INTERFACE AND ITS EVOLUTION. - Ishii, Hiroshi (Communications of the ACM, 2008)
The article discusses tangible computer user interfaces (TUIs). Contrary to graphical user interfaces that decouple the input and presentation of data, a TUI manifests digital information in physical form. The author illustrates the concept by describing two implementations. An "Urban Planning Workbench" developed in 1999 by the Tangible Media Group incorporated TUI using scaled models of buildings. Tangible Media later developed "Sandscape," a TUI that permitted users to manipulate a model landscape by handling sand.